RISK ANALYSIS ON THE IMPLEMENTATION OF THE CONSTRUCTION PROJECT OF THE HIGH PROSECUTOR'S OFFICE OF SOUTH KALIMANTAN PROVINCE (CONTINUED) - Verdiyani, Irwina Sari; Karim, Abdul (Universitas Lambung Mangkurat, 2025)
The change in the status of the capital city of South Kalimantan province has implications for the development of urban infrastructure. Various construction works are being carried out, such as the construction of buildings, roads, and bridges. In the implementation of a construction project, of course, there is never a risk that can hinder the implementation process wherever the project is carried out. For example, the South Kalimantan Provincial High Prosecutor's Office (Continued) project is one of the medium-risk projects.The method used for this risk analysis is to use a quantitative research method with validity and reliability tests. Then analyze the Probability and Impact data using the Severity Index calculation, which further determines the level of risk with the Matrix Probability and Impact. Then categorize these risk variables into risk acceptance scales in order to obtain the dominant risk variables that occur in the project.The results of the research from the risk analysis on the Implementation of the South Kalimantan Provincial High Prosecutor's Office Development Project (Continued) obtained 15 valid risk variables. There were 11 dominant risk variables with medium categories and 3 risks with high categories that affected the projectKeywords: Risk, Risk Analysis, Building, Severity Index